Harmonisation of Modern Truth Theory and Islamic Epistemology: A Transformative Epistemological Review of the Contemporary Truth Crisis - Irfa Maalina Li'Illiyyina (Averroes: Journal for Science and Religious Studies, 2026)
Background Study: This article examines the problem of truth in contemporary society by focusing on the harmonization between modern Western theories of truth and Islamic epistemology. The study addresses the following questions: how do classical and modern theories of truth explain the nature of truth, what challenges arise in the era of post-truth and digital disinformation, and how can Islamic epistemology contribute to resolving these challenges? Methods: Employing a qualitative literature review method, the article analyzes major theories of truth—correspondence, coherence, pragmatism, consensus, and performative theories—alongside the Islamic concept of al-ḥaqq, including rational, empirical, intuitive (ḥudūrī), and revelational sources of knowledge. Key Findings: The findings indicate that no single theory sufficiently addresses contemporary epistemic crises, particularly when knowledge is detached from ethical responsibility. The study proposes a dialogical and integrative framework that harmonizes rational-empirical verification with moral-spiritual orientation. Contribution: The main contribution of this article lies in formulating a transformative ethical-epistemic model of “civilized truth,” which integrates universal ethics and Islamic values to strengthen social responsibility in the digital age. Conclusion: In conclusion, a pluralistic and harmonize epistemology is essential to address post-truth challenges and to restore truth as a foundation for justice, public trust, and social cohesion.